2013
DOI: 10.1093/schbul/sbt079
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure in Individuals at Clinical High Risk of Psychosis: A Whole-Brain Diffusion Tensor Imaging Study

Abstract: Background:The study of individuals at clinical high risk (CHR) for psychosis provides an important opportunity for unraveling pathological mechanisms underlying schizophrenia and related disorders. A small number of diffusion tensor magnetic resonance imaging (DTI) studies in CHR samples have yielded anatomically inconsistent results. The present study is the first to apply tract-based spatial statistics (TBSS) to perform a whole-brain DTI analysis in CHR subjects. Methods: A total of 28 individuals meeting C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 40 publications
18
65
0
Order By: Relevance
“…The forceps major communicates somatosensory information be tween the parietal and occipital lobes via the splenium, a struc ture shown to be impaired in individuals at early and later stages of psychosis 1 as well as ultrahigh risk individuals. 53 A re port by Waltz and colleagues 54 demonstrated that individuals with schizophrenia showed a selective deficit in the ability to learn from positive outcomes but no deficits in learning from negative outcomes. This motivational deficit correlated with negative symptoms but not with neuropsychological measures of working memory, suggesting that the observation was not a neuropsychological deficit.…”
Section: Discussionmentioning
confidence: 99%
“…The forceps major communicates somatosensory information be tween the parietal and occipital lobes via the splenium, a struc ture shown to be impaired in individuals at early and later stages of psychosis 1 as well as ultrahigh risk individuals. 53 A re port by Waltz and colleagues 54 demonstrated that individuals with schizophrenia showed a selective deficit in the ability to learn from positive outcomes but no deficits in learning from negative outcomes. This motivational deficit correlated with negative symptoms but not with neuropsychological measures of working memory, suggesting that the observation was not a neuropsychological deficit.…”
Section: Discussionmentioning
confidence: 99%
“…6 Both a neurodevelopmental model, 7,8 implying that WM alterations are present before disease onset and a postonset progression model, indicating that structural brain abnormalities progress over time after disease onset, have been proposed. 9,10 In support of the neurodevelopmental model, several cross-sectional DTI studies have revealed microstructural WM alterations in frontotemporal and -parietal connections in first-degree relatives without symptoms, 11,12 in clinical high-risk populations before onset, 13,14 and in patients with early onset psychosis. 15 Indeed, the lifetime trajectory of WM alterations in schizophrenia suggests higher percentages of WM loss in the first years of the illness, implicating altered neurodevelopment.…”
Section: Introductionmentioning
confidence: 91%
“…40 However, their method involved hypothesisfree whole brain white matter group comparisons, and, therefore, might not have been sufficiently sensitive to detect subtle changes in the thalamo-cortical white matter connections.…”
Section: Introductionmentioning
confidence: 99%